Positive Psychological Assessment: A Handbook of Models and Measures (2nd Ed.). 2019
DOI: 10.1037/0000138-020
|View full text |Cite
|
Sign up to set email alerts
|

Gratitude.

Abstract: S ince the first edition of this handbook was published, rapid progress has been made in the science of gratitude, due in large part to advances in measurement. In this chapter we describe these recent developments in the measurement of gratitude across the lifespan. We emphasize self-reported gratitude measures, since these have dominated research.Efforts to develop measures of gratitude have increased as accumulating research has demonstrated that gratitude is foundational to well-being and mental health thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 46 publications
(60 reference statements)
2
34
0
Order By: Relevance
“…Dogs are thought of as family members and many people express concerns about their dog before they consider their own needs. Gratitude regarding their dog was a dominant theme emanating from the participants, and empirical studies have demonstrated that gratitude can reduce negative mental health symptoms [ 44 , 45 ]. Through the uncertainties, fears, and losses resulting from the pandemic, canine companions offer meaning, comfort, and a hopeful distraction from the unsettling feelings of our daily lives.…”
Section: Discussionmentioning
confidence: 99%
“…Dogs are thought of as family members and many people express concerns about their dog before they consider their own needs. Gratitude regarding their dog was a dominant theme emanating from the participants, and empirical studies have demonstrated that gratitude can reduce negative mental health symptoms [ 44 , 45 ]. Through the uncertainties, fears, and losses resulting from the pandemic, canine companions offer meaning, comfort, and a hopeful distraction from the unsettling feelings of our daily lives.…”
Section: Discussionmentioning
confidence: 99%
“…Once included in the SEM model, situational moral emotions cease to have a significant effect on prosociality towards victims. According to the literature, dispositional gratitude appears as a stable tendency to be grateful under different circumstances and promotes positive relationships (Emmons et al, 2019). Therefore, from this perspective, the constant experience of gratitude could promote social integration and social support in adolescence (Marshall et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…Scientific studies that assess emotions make a clear distinction between dispositional emotions, which are considered almost personality traits that remain stable over time, and situational emotions, which are experienced in specific social situations (Emmons et al, 2019;Emmons & McCullough, 2004). This debate has also been highlighted in studies regarding the development of moral emotions (Malti et al, 2020).…”
Section: Dispositional and Situational Moral Emotions And Their Assessmentmentioning
confidence: 99%
“…Gratitude emerges as a construct of interest in the field of mental health. It has been described as a variable related to happiness, health, purpose in life, and other desirable life outcomes but also related to a decrease in negative affect and vice versa ( Rash et al, 2011 ; Emmons et al, 2019 ). According to Syropoulos and Markowitz (2020) , gratitude is related to various behavioral, affective, and attitudinal responses to the pandemic.…”
Section: Introductionmentioning
confidence: 99%